Exploration of a therapeutic strategy for osteogenesis imperfecta - McMahon, Helena (Trinity College (Dublin, Ireland). Department of Genetics, 2007)
The studies described in this thesis focus upon an RNAi-base therapeutic approach for the treatment of Col1A1 linked Osteogenesis Imperfecta (OI). OI is an autosomal dominant negative disorder in w hich the presence of mutated α1 (I) or α1 (2) chains in the type I collagen triple results in the form ation of weak and brittle bones. It is genetically heterogeneous w ith over 350 mutations in the Col1a1 and Col1a2 genes known to cause OI. As it would not be feasible to design effectors of RNAi to target every OI linked mutation, a mutation independent approach termed suppression and replacement was undertaken, this involves targeting the wild type coding sequence of the Col1a1 gene. This should result in suppression of both Col1a1 alleles; consequently it is likely that a replacement Col1a1 gene would be required to restore the levels of Col1a1 expression to close to wild type levels. This replacement gene would have to be engineered such that it is protected from the Col1a1 targeting RNAi effectors.
Keywords: Genetics, Ph.D.; Ph.D. Trinity College Dublin